The Influence of Influencer Marketing on Generation Z's Purchase Decision of Somethinc Products Through Perceived Value and Price Sensitivity - Putri Berlian Apriliyani; Mohamad Rifqy Roosdhani (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
This study investigates the impact of influencer marketing on the buying choices of Generation Z consumers for Somethinc products, emphasizing the role of perceived value and price sensitivity as mediators. Utilizing influencer marketing is now crucial, especially with the beauty industry's shift to digital media and the high rate of social media adoption in Indonesia. Employing a quantitative methodology, this research collected primary data via structured surveys. A purposive sample of 133 Indonesian Generation Z buyers (aged 13-28) of Somethinc items was analyzed. SmartPLS 4.0 was applied to assess the structural and measurement models. Results show that influencer promotional efforts directly and positively affect purchase intent, price sensitivity, and perceived value. Additionally, price sensitivity and perceived value serve as successful mediators connecting influencer marketing to final purchasing actions.